Cost-effectiveness evaluation of routine histoplasmosis screening among people living with advanced HIV disease in Latin America and the Caribbean. - Radha Rajasingham; Narda Medina; Gabriel T Mousquer; Diego H Caceres; Alexander Jordan; Mathieu Nacher; Diego R Falci; Ayanna Sebro; Alessandro C Pasqualotto; Omar Sued; Tom Chiller; Freddy Perez (PLOS Global Public Health)
Histoplasma antigen can be detected in people with advanced HIV disease (AHD), allowing for early and accurate diagnosis of histoplasmosis. The aim of this analysis was to assess the cost-effectiveness of routine histoplasmosis screening using antigen detection, among people with AHD. We developed a decision analytic model to evaluate Histoplasma antigen screening among people with AHD. The model estimated the costs, effectiveness, and cost-effectiveness of routine screening for Histoplasma antigen compared to the current practice of no routine Histoplasma antigen screening. The model includes stratification by symptoms of histoplasmosis, severity of presentation, and estimates of 30-day mortality. Data sources were taken from the Pan American Health Organization (PAHO) Strategic Fund databases on public purchases of medicines, and published literature on treatment outcomes. Outcome measures are life years saved (LYS), costs (US dollars), and incremental cost-effectiveness ratios (ICERs). Routine Histoplasma antigen screening avoids an estimated 17% of deaths in persons with advanced HIV disease, and is cost-effective compared to no histoplasmosis screening, with an ICER of $26/LYS. In sensitivity analysis assuming treatment for histoplasmosis with liposomal amphotericin, Histoplasma antigen screening remains cost-effective with an ICER of $607/LYS. Histoplasma antigen screening among people with AHD is a cost-effective strategy and could potentially avert 17% of AIDS-related deaths. Prospective evaluation of histoplasmosis screening is warranted to determine effectiveness and treatment outcomes with this strategy.